Idoso e cidade a pé: avaliação dos padrões de caminhabilidade em uma área urbana de João Pessoa, Paraíba - Silva, Paulo Roberto de Oliveira (2024)
The precarious walking conditions in our cities are largely the result of a car-oriented urban planning approach that does not prioritize pedestrians. This problem is even worse for the elderly population, which, although growing, faces greater restrictions when walking. This dissertation aims to understand the relationship of the elderly with urban mobility, investigating physical, environmental, and social factors associated with the walkability of this group. The pedestrian infrastructure of the IBGE census sector (2010) with the highest number of elderly people in the city of João Pessoa, Paraíba, was the object of study for this research. Initially, a Segment Angular Analysis (SAA) was conducted to identify the road segments most used by pedestrians in this spatial cutout. Next, a Behavioral Analysis was carried out through behavioral mapping, photographic surveys, and searching for urban traces. Subsequently, the Elderly Walkability Index (EWI) was constructed and applied in this spatial cutout, drawing from other walkability indices that address the elderly, allowing the identification of the facilities and challenges faced during pedestrian movement across different categories and attributes. Finally, the EWI categories and attributes were evaluated and weighted through the application of questionnaires with the elderly. The index results reveal the existence of basic infrastructure for walkability in the study area, but with a need for improvement in all explored categories. The questionnaire results demonstrated the elderly's dissatisfaction with the quality of public spaces and some discrepancies concerning the EWI scores.